2017
DOI: 10.1017/s0007114517001878
|View full text |Cite
|
Sign up to set email alerts
|

Does a better adherence to dietary guidelines reduce mortality risk and environmental impact in the Dutch sub-cohort of the European Prospective Investigation into Cancer and Nutrition?

Abstract: Guidelines for a healthy diet aim to decrease the risk of chronic diseases. It is unclear as to what extent a healthy diet is also an environmentally friendly diet. In the Dutch sub-cohort of the European Prospective Investigation into Cancer and Nutrition, the diet was assessed with a 178-item FFQ of 40 011 participants aged 20–70 years between 1993 and 1997. The WHO’s Healthy Diet Indicator (HDI), the Dietary Approaches to Stop Hypertension (DASH) score and the Dutch Healthy Diet index 2015 (DHD15-index) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 41 publications
6
65
0
2
Order By: Relevance
“…Of the 13 related publications, one publication reported the results in two different cohort studies and therefore, was considered as two separate studies [34]. Finally, 17 prospective cohort studies (13 publications) were included in the final analyses [22,23,33,34,[36][37][38][39][40][41][42][43][44]. Three studies (two publications) did not provide sufficient data regarding the number of deaths and risk of mortality based on each category (quartile or quintile) of the DASH diet score; thus, they were not included in the non-linear dose-response meta-analysis [34,40].…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 13 related publications, one publication reported the results in two different cohort studies and therefore, was considered as two separate studies [34]. Finally, 17 prospective cohort studies (13 publications) were included in the final analyses [22,23,33,34,[36][37][38][39][40][41][42][43][44]. Three studies (two publications) did not provide sufficient data regarding the number of deaths and risk of mortality based on each category (quartile or quintile) of the DASH diet score; thus, they were not included in the non-linear dose-response meta-analysis [34,40].…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Eleven studies were from the US [22, 23, 33, 36-39, 41, 44], four studies were from Europe [40,42,43], and two studies (one publication) were from Asia [34]. From 17 prospective cohort studies included in this meta-analysis: 13 studies (nine publications) reported data for allcause mortality [23,33,34,36,[38][39][40][41][42][43], 12 studies (nine publications) reported CVD mortality [22,23,[36][37][38][39][40][41]43], 12 studies (seven publications) reported total cancer mortality [22,23,36,[38][39][40][41], and two studies reported stroke mortality [37,44]. All included studies used a validated food frequency questionnaire to assess dietary intakes except two studies that evaluated dietary intakes using 3-day dietary records [36].…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To exclude dietary over and under reporters, participants in the highest and lowest 0.5% of the ratio of reported energy intake to basal metabolic rate were also excluded (n = 400). Participants with a self-reported history of cancer (n = 1645), diabetes (n = 793), myocardial infarction (n = 531), or stroke (n = 463) at baseline were excluded to include the same population as our previous publications (Biesbroek et al 2014;Biesbroek et al 2017). After these exclusions, 36,209 participants remained for analysis.…”
Section: Study Populationmentioning
confidence: 99%
“…The observed increase in DHD15-index score (men scored 7 points higher and women 8·5) is relevant for public health. In a previous study with baseline data of EPIC-NL we observed that per 1  sd increase in the DHD15-index score (16 points), the overall risk of mortality was 12 (95 % CI 5, 18) % lower in men and 8 (95 % CI 4, 12) % lower in women ( 37 ) .…”
Section: Discussionmentioning
confidence: 87%